Aki and Friends - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2013)
Aki, a man enamoured with life and enchanted by animals – including humans of different varieties – pays a visit to his friend, the veterinarian. The vet tells him of two seniors who suffer from depression, and Aki is quick to raise their spirits and warm up their aching bodies. He hangs the boa constrictor on his neck and places the hairy tarantula on his head. There is no need to worry, he assures us. After all, why would two elderly creatures hurt an empathetic being so eager to help them? This view was typical of Aki. That is how he viewed the world, its history and conflicts – as well as the solutions for those conflicts. 'Just think about it logically', he says. 'Why would a Palestinian suddenly turn into a "terrorist"? What reason does he have to oppose "peace"? Why should he be eager to fight the "only democracy in the Middle East"? Is it his culture, religion or race? Is it "in his nature", as the Zionist propaganda machine reiterates?' Of course not, he answers. For more than a century, the Palestinians have confronted a Zionist movement whose colonial policies have gradually deprived them of their life, land and autonomy. As often happens with occupiers, the Israelis have preferred to blame their victim. Their fancy academic theories, spiced up with ideologies of culture, religion and race, prove, at least to themselves, that there can be no 'political solution'. The 'Arabs', they say, cannot be trusted. Like the boa constrictor and tarantula, it is 'their nature' to bite and strangle. Nowadays, these explanations have no traction. Most sensible observers around the world have come to accept Aki's logic and reject the official Israeli line as self-serving, if not ludicrous. But that wasn't always the case. Half a century ago, when Aki and his friends started their hazardous journey to explore the underlying logic of the conflict, they were considered illogical, if not weird, and branded as 'traitors' (although it was never clear exactly what or who they had 'betrayed').
Keywords: 330; Akiva Orr; autonarchy; biography; capitalism; consciousness; democracy; Israeli-Palestinian conflict; history; MATZPEN; science and church